Advantages of breast cancer visualization and characterization using synchrotron radiation phase‐contrast tomography. (14th August 2018) - Pacilè, Serena; Baran, Patrycja; Dullin, Christian; Dimmock, Matthew; Lockie, Darren; Missbach-Guntner, Jeannine; Quiney, Harry; McCormack, Mikkaela; Mayo, Sheridan; Thompson, Darren; Nesterets, Yakov; Hall, Chris; et al.
Abstract : This proof‐of‐concept study demonstrates that in‐line propagation‐based phase‐contrast computed tomography of fresh tissues and complete breast specimens can be performed. High‐quality images can be obtained using an X‐ray dose low enough to allow for a future application in patients, while providing a more accurate characterization of the clinical picture. Abstract : The aim of this study was to highlight the advantages that propagation‐based phase‐contrast computed tomography (PB‐CT) with synchrotron radiation can provide in breast cancer diagnostics. For the first time, a fresh and intact mastectomy sample from a 60 year old patient was scanned on the IMBL beamline at the Australian Synchrotron in PB‐CT mode and reconstructed. The clinical picture was described and characterized by an experienced breast radiologist, who underlined the advantages of providing diagnosis on a PB‐CT volume rather than conventional two‐dimensional modalities. Subsequently, the image quality was assessed by 11 breast radiologists and medical imaging experts using a radiological scoring system. The results indicate that, with the radiation dose delivered to the sample being equal, the accuracy of a diagnosis made on PB‐CT images is significantly higher than one using conventional techniques.